Menelisik Tafsir Ibnu Katsir dalam Mushaf Aisyah: Studi Wacana atas Reproduksi Nalar Patriarkis dalam Terjemahan Al-Qur’an untuk Wanita - Fathassururi, Fathassururi; Rahman, Fathur; Lismana, Ilman; In, Khurin; Nadia, Intan (UIN Sultan Syarif Kasim Riau, 2025)
This study aims to examine the process of women’s objectification and the perpetuation of patriarchal reasoning within the Mushaf Aisyah, with particular emphasis on the intertextual relationship between Tafsir Ibn Kathir and the Qur’anic verses highlighted in pink. The primary research questions investigate the patterns and mechanisms through which patriarchal interpretations are transmitted from Tafsir Ibn Kathir into the Mushaf Aisyah, as well as the degree to which its summarized exegeses reproduce or transform classical conceptions of women’s roles and status in Islam. Employing a qualitative methodology grounded in library research, the study utilizes a descriptive-analytical and intertextual approach. The data sources include the Mushaf Aisyah, Tafsir Ibn Kathir, and both classical and contemporary literature on Qur’anic exegesis and gender studies. The analysis centers on verses pertaining to women marked in pink addressing themes such as creation, leadership, inheritance, and social status. The findings indicate that the Mushaf Aisyah reproduces and reinforces patriarchal reasoning through selective citation and gender-biased interpretation derived from Tafsir Ibn Kathir. The transmission mechanisms manifest in three forms: First, symbolic highlighting of women-related verses in pink, second, citation of classical commentary without critical reinterpretation, and third, incorporation of female-related hadiths from Bukhari and Muslim. The study concludes that the Mushaf Aisyah emphasizes symbolic feminine aesthetics rather than critically challenging entrenched patriarchal biases. This study theoretically advances the discourse on gender exegesis and contemporary Qur’anic manuscript studies in Indonesia by elucidating the ideological underpinnings associated with the commodification of sacred texts.Abstrak: Penelitian ini bertujuan menganalisis proses objektivasi perempuan dan reproduksi nalar patriarkis dalam Mushaf Aisyah, khususnya melalui intertekstualitas antara Tafsir Ibnu Katsir dan ayat-ayat yang diberi penanda warna merah muda. Pertanyaan utama yang dikaji adalah bagaimana pola dan mekanisme transmisi nalar patriarkis dari Tafsir Ibnu Katsir ke dalam Mushaf Aisyah, serta sejauh mana ringkasan tafsir tersebut mereproduksi atau memodifikasi pemahaman klasik tentang peran dan kedudukan perempuan dalam Islam. Penelitian ini menggunakan metode kualitatif berbasis studi pustaka dengan pendekatan deskriptif-analitis dan analisis intertekstual. Data dikumpulkan dari Mushaf Aisyah, Tafsir Ibnu Katsir, serta literatur tafsir dan studi gender kontemporer. Analisis difokuskan pada ayat-ayat bertema perempuan yang ditandai dengan warna merah muda, mencakup isu penciptaan, kepemimpinan, kewarisan, dan kedudukan sosial perempuan. Hasil penelitian menunjukkan bahwa Mushaf Aisyah mereproduksi dan memperkuat nalar patriarkis melalui seleksi ayat dan interpretasi yang bias gender dari Tafsir Ibnu Katsir. Mekanisme transmisinya tampak dalam tiga bentuk:Pertama, penandaan simbolik ayat bertema perempuan dengan warna merah muda, kedua, pengutipan ringkasan tafsir klasik tanpa reinterpretasi kritis, dan ketiga, penyisipan hadis-hadis perempuan dari riwayat Bukhari-Muslim. Penelitian ini menegaskan bahwa Mushaf Aisyah lebih menampilkan estetika femininitas simbolik daripada menghadirkan dekonstruksi terhadap bias patriarkis yang telah mapan. Secara teoretis, penelitian ini berkontribusi pada kajian tafsir gender dan studi mushaf kontemporer di Indonesia dengan mengungkap dimensi ideologis di balik komodifikasi teks suci.